PENGARUH STRUKTUR MODAL TERHADAP RETURN SAHAM DAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Nurwanto; Nugroho Mardi Wibowo; Hadi Susanto (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This study aims to describe the capital structure, profitability and stock returns of Mining Companies listed on the IDX, to examine and analyze the effect of capital structure on Company profitability, the effect of profitability and capital structure on Company stock returns, the effect of capital structure on stock returns through Company profitability.This research is an associative research with a quantitative approach. The population in this study were mining companies that were registered and actively traded on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sampling technique used in this study was purposive sampling so that 10 companies were obtained as research samples. This study uses PLS as a confirmatory theory and to analyze the effect or test the proposed hypothesis. The results of the study found that the average DER movement in mining companies tends to decrease. The average movement of ROA in mining companies has increased every year. The average movement of stock returns has decreased. The capital structure shows negative and significant results on profitability. Profitability shows positive and insignificant results on stock returns. The capital structure shows a negative and not significantly significant result on stock returns on. The capital structure shows a negative and significantly significant result on stock returns through profitability at Mining Companies Listed on the IDX in 2017-2021